STUDI FITOKIMIA DAN AKTIVITAS FARMAKOLOGI DARI KULIT BATANG MESOYI (Massoia aromatica Becc.) - Resha Rosalia; Devia Setyaningsih; Aghnia Ahda; Salma Aziz; Siti Lulu Luthfiah; Vera Dwi Apriani; Sri Tantia Dinita; Yuliani Dewi; Mira Oktaviani Malik (Jurnal Buana Farma, 2022)
For a long time, nature with all its wealth has been used by humans as a necessity of life including medicine. Today, traditional medicine with the use of plants is much in demand by people all over the world. One of the benefits-rich plants commonly used is the skin of the mesoyi stem (Messoia aromatica Becc.) which phytochemically contains flavonoid compounds, phenolics, alkaloids, steroids, triterpenoids, saponins, tannins, calcons, and coumarins. Based on pharmacological studies this plant can act as antimicrobial, phagocytic, cytotoxic, anti-inflammatory, immunomodulatory, antioxidant, analgetic, as well as other effects by inhalation. However, if further research is done, there may be more pharmacological activity resulting from this plant. Therefore, research on this plant still needs to be developed so that it can be used as a reference for traditional medicine.